Performance and Reliability Analysis of Current Transformer (CT) Type Iosk170 In The Ampel 500/150kv Substation Project: Case Study Of Line Up Mojosongo 2 - Hakiki, Riean Noer; Djuniadi, Djuniadi (Jurnal Teknik Elektro Indonesia, 2025)
The Ampel 500/150 kV Main Substation (GI) Project is an important initiative in the development of electricity infrastructure in Indonesia, with a strategic role in ensuring continuity and reliability of electricity supply. This research analyzes the performance and reliability of the IOSK170 type Current Transformer (CT) on the Mojosongo 2 Line Up at GI 500/150 kV Ampel. Tests show very high insulation resistance values, exceeding 300 GΩ for primary to ground and primary to secondary, and more than 2 GΩ for secondary to ground, indicating excellent insulation conditions. Winding resistance meets design specifications without significant damage. The transformation ratio test showed very small errors, between -0.071% to 0.047%, and the results were “OK” in the polarity test, ensuring accurate current transformation. RDC and V-Knee Point exhibit high resistance and sufficient values ​​for measurement and protection applications. Low ground resistance ensures good connectivity to the grounding system. Overall results show that the IOSK170 type CT has high reliability and performance according to industry standards, supporting the efficiency and reliability of the electric power system in Indonesia. These findings form the basis of recommendations for improving routine maintenance and testing procedures, as well as guidelines for future development of CT technology, essential for the continuity of a stable and safe electricity supply.